2014
DOI: 10.1111/acem.12445
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prehospital 12-Lead Electrocardiography and Treatment Times Among ST-Elevation Myocardial Infarction Patients With Atypical Symptoms

Abstract: Objectives: Guidelines advise that a prehospital electrocardiogram (ECG) should be obtained in any patients with chest pain, yet up to 20% of patients with ST-elevation myocardial infarction (STEMI) do not present with chest pain. The objective was to determine the association of atypical presentations in the prehospital setting on the likelihood of receiving a prehospital ECG and subsequent time to reperfusion therapy.Methods: This study used a data set that linked prehospital medical information from a state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(21 reference statements)
1
8
0
1
Order By: Relevance
“…A comparison of our findings with other published studies is difficult because the few studies that have examined EMS treatments by gender have not adequately controlled for important confounders such as EMS capacity (Bush et al, 2013;Cannon et al, 2014;Tataris et al, 2015), age, and race (Benson et al, 1997;Cannon et al, 2014;Rothrock et al, 2000). Controlling for patient demographic characteristics and hospital referral region, Bush et al (2013) reported an ECG rate difference between women and men who presented with CP of À1.7%, identical to that observed in our cohort.…”
Section: Discussionsupporting
confidence: 62%
“…A comparison of our findings with other published studies is difficult because the few studies that have examined EMS treatments by gender have not adequately controlled for important confounders such as EMS capacity (Bush et al, 2013;Cannon et al, 2014;Tataris et al, 2015), age, and race (Benson et al, 1997;Cannon et al, 2014;Rothrock et al, 2000). Controlling for patient demographic characteristics and hospital referral region, Bush et al (2013) reported an ECG rate difference between women and men who presented with CP of À1.7%, identical to that observed in our cohort.…”
Section: Discussionsupporting
confidence: 62%
“…We supposed that the criteria needed to be simple and easy to understand to avoid underestimations of STEMI before the implementation of prehospital ECG transmission, with the inclusion of not only typical chest pain but also atypical symptoms, such as syncope or general fatigue [19]. The ECG transmission criteria were created using the chief complaints of consecutive STEMI patients according to past medical records in our hospital between 2006 and 2013.…”
Section: Establishment Of Prehospital Ecg Transmission In the Presentmentioning
confidence: 99%
“…demonstrated that over one-quarter of STEMI patients presented without chest pain and did not receive a prehospital ECG. [29] Atypical presentations were common in our study, with classic STEMI recognition characteristics (pain, nausea, dyspnea) not present in many cases. Almost 50% of the patients in our study had a pain scale under 5, and many had no pain on assessment.…”
Section: Discussionmentioning
confidence: 75%